FRI0651 Observational reproducibility study of uco-track©, an automatized measurement of mobility, in patients with axial spondyloarthritis. (15th June 2017) - Garrido, J; Collantes, E; Mulero, J; Flores, B; Zarco, P; Mazzucchelli, R; Domínguez-González, M; Carmona, L; Cea-Calvo, L; Arteaga, M; Curbelo, R
Abstract : Background: The classical measures of spinal mobility for the assessment of patients with axial spondyloarthritis (SpA), such as BASMI, are subject to inter-observer variability. Objectives: We assessed the reproducibility of the UCOASMI index (University of Cόrdoba Ankylosing Spondylitis Metrology Index), a composite index of cervical and spinal mobility obtained with the UCOTrack © motion analysis system (an innovative 3D motion capture system based on video-images) [1], in patients with axial SpA. Methods: An observational study of repeated measures was carried out in 3 Spanish centers with the technology available (H. Reina Sofía, Cόrdoba, H. Puerta de Hierro, Madrid and H. Fundaciόn Alcorcόn, Madrid). For the assessment of intra-observer reliability, 30 patients (10 per center) were evaluated twice, 3–5 days apart. For the inter-observer reliability, 9 patients were evaluated in the 3 centers by 3 observers (window 3–7 days). The Intraclass Correlation Coefficients (ICC) for UCOASMI and classical metrology measurements were calculated. Results: We included 30 patients (73% men, mean age 52 [SD 9], mean BASDAI 3.3 [SD 2]). The table shows the intra- and inter-observer reliability values. The reproducibility of UCOASMI was very high, with inter-observer ICC 0.99, and intra-observer ICC 0.97, 0.97 and 0.99, higher than most conventional measurements. The Schober test and cervical rotation showed lower reproducibility (inter-observer ICC between 0.58 and 0.68) and variable intra-observer ICC. Conclusions: The reproducibility of the UCOASMI, obtained through the UCOTrack © motion analysis system in the 3 centers, was very high, in contrast to the lower reproducibility of the Schobert test and other measures of classical metrology. The reliability of this system opens the door to using this technology to monitor SpA patients and in future research studies. References: Garrido-Castro JL, Escudero A, Medina-Carnicer R, et al. Validation of a new objective index to measure spinal mobility: the University of Cordoba Ankylosing Spondylitis Metrology Index (UCOASMI). Rheumatol Int 2014;34:401–6. Acknowledgements: Funded by MSD, Spain. Disclosure of Interest: None declared